2018
DOI: 10.1242/jeb.171199
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic characteristics along the wing span of a dragonflyPantala Flavescens

Abstract: We investigated the characteristics of interwing aerodynamic interactions across the span of the high aspect ratio, flexible wings of dragonflies under tethered and free-flying conditions. This revealed that the effects of the interactions on the hindwings vary across four spanwise regions. (i) Close to the wing root, a trailing-edge vortex (TEV) is formed by each stroke, while the formation of a leading-edge vortex (LEV) is limited by the short translational distance of the hindwing and suppressed by the fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 51 publications
4
37
0
Order By: Relevance
“…Since significant ecological and climatic differences arise across biomes, the range of zones dominated by a species can provide us with information linked to dispersal capacity and environmental tolerance (Renner et al, 2019). In some cases, this distribution pattern may be related to morphological traits of these species, such as body size, or even the shape, size, and venation of the wings (Hefler et al, 2018; Wootton, 2020). In fact, morphology has been considered an important element to understand the biological mechanisms of the group.…”
Section: Discussionmentioning
confidence: 99%
“…Since significant ecological and climatic differences arise across biomes, the range of zones dominated by a species can provide us with information linked to dispersal capacity and environmental tolerance (Renner et al, 2019). In some cases, this distribution pattern may be related to morphological traits of these species, such as body size, or even the shape, size, and venation of the wings (Hefler et al, 2018; Wootton, 2020). In fact, morphology has been considered an important element to understand the biological mechanisms of the group.…”
Section: Discussionmentioning
confidence: 99%
“…Aeroelastic loading of the wing during flight causes complex deformation of the architecture (e.g., Wootton et al, 1998;Norris et al, 2010;Lu et al, 2010, Jongerius andLentink, 2010). The flow patterns which have been observed on the wings of dragonflies during flight are similarly complex ( (e.g., Thomas et al, 2004;Wang & Sun, 2005;Bomphrey et al, 2016;Li and Dong, 2017;Bode-Oke at al., 2017;Bode-Oke et al, 2018;Hefler et al, 2018;Shumway et al, 2020). We expect the local placement and overall density of wing sensors is critical for capturing relevant information.…”
Section: A Complete Sensor Map Of Odonata Wingsmentioning
confidence: 99%
“…In contrast, Bomphrey et al 29 used a particle image velocimetry (PIV) experiment to study the flow pattern generated by a freeflying dragonfly. The recent studies on the free-flying dragonfly [30][31][32] explore different interaction mechanisms of the forewing and hindwing and its impact on lift and thrust generation along the span-wise by using CFD and PIV techniques. It has been shown that the hindwing thrust is extremely sensitive towards the forewing-hindwing interaction, and the magnitude of this force spreads equally at the central span of the wing.…”
Section: Introductionmentioning
confidence: 99%